International practices for assessing working conditions and social guarantees at occupational risks - Yensebayeva, А.Р.; Yagmussova, А.Ф.; Baiterekova, К.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
In the context of globalization and technological development, the issues of labor conditions classification, occupational risk assessment, and ensuring social guarantees for workers engaged in hazardous and harmful working conditions are of particular relevance. The aim of this study is to analyze international experience in labor classification and risk assessment and to examine its impact on employees social guarantees. The focus is on the approaches applied in the European Union, the United States, and the CIS countries. The scientific significance of the study lies in identifying patterns of legal regulation of labor rights protection in different jurisdictions. The practical significance is determined by the possibility of applying international experience to improve the national legislation of the Republic of Kazakhstan. This study relies on comparative legal analysis, systematic and statistical approaches, along with legal modeling methods. The study identifies key trends in international regulation, including a differentiated approach to risk assessment, compensation mechanisms, and social protection. The results obtained make it possible to formulate recommendations for improving the system of social guarantees for workers in Kazakhstan, considering the best global practices. This research contributes to the development of labor law and social policy, enhancing the level of workers' rights protection.